GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI PENGRAJIN GERABAHPEMBERDAYAAN EKONOMI - Innes Maeya Sofa; Wiwik Widayati; Supratiwi . (Journal of Politic and Government Studies, 2014)
Economic empowerment that involves the participation of society at large , makes a lot of SME ( Small Medium Enterprises ) that grow and evolve , becoming even safety valve for the nation's economic recovery . This is a popular economic sector entities as economic actors who have proven not only to survive , even say " savior " in times of crisis , because of its ability to provide a significant contribution to the GDP ( Gross Domestic Product ) and employment. The tendency of the ability of SMEs ( Small Medium Enterprises ) to contribute significantly to the economic development of the country , not only in Indonesia and developing countries , but also occurs in developed countries . For example Bantul , through cooperation with the private sector is able memandirikan Bantul through the development of SMEs ( Small and Medium Enterprises ) . Kasongan pottery craftsmen case is one example of an area that locality makers of pottery items as the subject of a wide range of economic empowerment as a basic policy concern for the Government of Bantul memandirikan pottery artisans and craftsmen with the basic spirit of eventual rate of growth industries including pottery be increased . Kasongan be a tourist village with pottery attraction . This is what should be in the example for other regions of Indonesia , especially in order to observe the development of SMEs (Small and Medium Enterprises ) .Keywords : economic empowerment , pottery craftsmen Kasongan Bantul